Vándorlások vizsgálata a szegedi agglomeráció egyik településén, 2010-ben - Zsótér, Brigitta; Nagy, Angéla (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
A questionnaire survey wa s made on the migration to Deszk from which it can be concludedthat the younge r and middle-.aged age group move to the settlement (65,19% migrated from Szeged).The reasons from migration are the low prices of plots and real estates and the peaceful environment.Most of the migrants work in Szeged and they used the settlement as a so-called ,.bedroomcommunity" . A significant number of respondents (239 persons) drive to work. According to theanalysis made by data of KSH, in the examined period (1999-2008) mortality exceeded birth rate, thenumber of marriages exceeded the numbe r of divorces. It can also be seen that more people migrate toSzeged and its catchment area than leave it.